2009
DOI: 10.1007/s12195-009-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Future of Orthopaedic Sports Medicine and Soft Tissue Healing: The Important Role of Engineering

Abstract: The practice of orthopaedic sports medicine, specifically the management of ligament and tendon injuries, will experience dramatic changes in the near future. Rapid technological advancements, especially in imaging, will greatly increase the speed and accuracy of diagnosing musculoskeletal injuries. On the contrary, effective treatment strategies will lag behind. This widening gap will offer huge opportunities for clinicians, basic scientists, and bioengineers to collaborate and work jointly on in depth basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 178 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…The sheep and goat have commonly been chosen as animal models for the knee [30][31][32][33] because of anatomical [34][35][36][37] and mechanical [38][39][40][41] similarities to human ACLs. These sheep were obtained from the Michigan Livestock Exchange, various farms in the area or intra-university transfer.…”
Section: Animal Model and Animal Carementioning
confidence: 99%
“…The sheep and goat have commonly been chosen as animal models for the knee [30][31][32][33] because of anatomical [34][35][36][37] and mechanical [38][39][40][41] similarities to human ACLs. These sheep were obtained from the Michigan Livestock Exchange, various farms in the area or intra-university transfer.…”
Section: Animal Model and Animal Carementioning
confidence: 99%
“…Additionally, transgenic porcine models of human disease are expected to provide a substantial contribution to the development of new treatments and drugs (Petters et al, 1997; Rogers et al, 2008; Umeyama et al, 2009). Genetically modified pigs that act as a source of organs/tissues for xenotransplantation or tissue engineering have also been investigated (Matsunari and Nagashima, 2009; Woo et al, 2009). Furthermore, transgenic pigs that can be used as bioreactors for producing therapeutic proteins may have a significant impact on the pharmaceutical industry (Van Cott et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular matrix bioscaffolds have been shown to promote tissue regeneration and the repair of ligaments. 5 , 6 , 49 , 80 A study by Woo et al 83 showed that utilizing a porcine small intestinal submucosa bioscaffold to heal a transected ACL following repair led to new tissue formation, significant reductions in anterior-posterior joint instability relative to ACL-deficient joints, and in situ forces of the new ACL similar in scale to those of an intact ACL.…”
Section: Future Direction: Substitutes and Biological Augmentationmentioning
confidence: 99%